Stability of SARS-CoV-2 in cold-chain transportation environments and the efficacy of disinfection measures - Peng, Shuyi; Li, Guojie; Lin, Yuyin; Guo, Xiaolan; Xu, Hao; Qiu, Wenxi; Zhu, Huijuan; Zheng, Jiaying; Sun, Wei; Hu, Xiaodong; Zhang, Guohua; Li, Bing; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Background: Low temperature is conducive to the survival of COVID-19. Some studies suggest that cold-chain environment may prolong the survival of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and increase the risk of transmission. However, the effect of cold-chain environmental factors and packaging materials on SARS-CoV-2 stability remains unclear. Methods: This study aimed to reveal cold-chain environmental factors that preserve the stability of SARS-CoV-2 and further explore effective disinfection measures for SARS-CoV-2 in the cold-chain environment. The decay rate of SARS-CoV-2 pseudovirus in the cold-chain environment, on various types of packaging material surfaces, i.e., polyethylene plastic, stainless steel, Teflon and cardboard, and in frozen seawater was investigated. The influence of visible light (wavelength 450 nm-780 nm) and airflow on the stability of SARS-CoV-2 pseudovirus at -18°C was subsequently assessed. Results: Experimental data show that SARS-CoV-2 pseudovirus decayed more rapidly on porous cardboard surfaces than on nonporous surfaces, including polyethylene (PE) plastic, stainless steel, and Teflon. Compared with that at 25°C, the decay rate of SARS-CoV-2 pseudovirus was significantly lower at low temperatures. Seawater preserved viral stability both at -18℃ and with repeated freeze‒thaw cycles compared with that in deionized water. Visible light from light-emitting diode (LED) illumination and airflow at -18℃ reduced SARS-CoV-2 pseudovirus stability. Conclusion: Our studies indicate that temperature and seawater in the cold chain are risk factors for SARS-CoV-2 transmission, and LED visible light irradiation and increased airflow may be used as disinfection measures for SARS-CoV-2 in the cold-chain environment.